2005
DOI: 10.1051/rnd:2005011
|View full text |Cite
|
Sign up to set email alerts
|

Declining fertility in the lethal yellow mouse is related to progressive hyperleptinemia and leptin resistance

Abstract: -Mice possessing the lethal yellow mutation (C57BL/6J A y /a) become obese and develop hyperleptinemia and leptin resistance as they age. To determine the relationship between altered leptin physiology and reproductive function in these mice, we compared body weight (BW), serum leptin concentration, ovulation rate, and in vitro blastocyst development among 120-and 180-d-old lethal yellow and black non-mutant (a/a) mice. Estrous female yellow and black mice were mated with fertile black males. Oviducts were flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…Conversely, our results indicate no effect or a positive effect of overnutrition (obesity) on the ovulation and fertilization rates. In accordance with our outcomes, several studies have reported that there are no differences in the number of collected and IVF produced oocytes or the number of isolated zygotes between obese and nonobese donors in both women and experimental animals [3,7,23,24]. There was no effect of overnutrition found on ovulation activity and fertilization rate in vivo and in vitro either in cows or ewes [25][26][27].…”
Section: The Effect Of Maternal Body Condition On Fertility and Lipidsupporting
confidence: 91%
“…Conversely, our results indicate no effect or a positive effect of overnutrition (obesity) on the ovulation and fertilization rates. In accordance with our outcomes, several studies have reported that there are no differences in the number of collected and IVF produced oocytes or the number of isolated zygotes between obese and nonobese donors in both women and experimental animals [3,7,23,24]. There was no effect of overnutrition found on ovulation activity and fertilization rate in vivo and in vitro either in cows or ewes [25][26][27].…”
Section: The Effect Of Maternal Body Condition On Fertility and Lipidsupporting
confidence: 91%
“…Subsequent studies then demonstrated that leptin replacement therapy rescued the sterility of genetically obese ob/ob male mice [17]. Experiments in obese mice possessing lethal yellow mutations (C57BL/6J-A y /a) demonstrated an association between reduced fertility, leptin resistance, and hyperleptinemia [18]. In contrast, high-fat diet consumption caused obesity in DBA/2J male mice; however, these mice exhibited no impairment in fertility despite enduring insulin resistance and hyperleptinemia [19].…”
Section: Introductionmentioning
confidence: 99%
“…Mice heterozygous for the Lethal Yellow (LY) mutation at the agouti gene locus exhibit distinct characteristics including yellow coat color, adult-onset obesity, insulin resistance (2), hyperleptinemia (3), and accelerated reproductive senescence (3,4). Declining ovarian function in aging LY mice is directly related to progressive obesity and hyperleptinemia (3).…”
Section: Introductionmentioning
confidence: 99%
“…Declining ovarian function in aging LY mice is directly related to progressive obesity and hyperleptinemia (3). Because of the adult-onset, progressive obesity characteristic of LY mice, these mice more closely mimic typical human obesity than many other mouse models of obesity, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation